PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KEPUASAN KERJA SERTA BERDAMPAK PADA KINERJA KARYAWAN DI HOTEL MURIA SEMARANG - Henry Yuliamir; Dyah Palupiningtyas; Enik Rahayu (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
This research was conducted at Hotel Muria Semarang which aims to analyze and describe the influence of competence and motivation on the performance of employees who are experiencing bad conditions because many of the competence of employees still as well as giving motivation is given less as the expectations of employees so turnover. Research data obtained through questionnaires and interviews. The sample used in this research is 114 respondents.The data obtained were processed by using descriptive analysis and quantitative statistical analysis. The result of regression analysis shows that the enhancement of competence and motivation on employee performance, and job satisfaction on the influence of competence and motivation will be followed by improvement of employee performance, and vice versa.